The CBC “Ventures in Citizenship” Broadcast of 9 November 1938 (Kristallnacht) - Neary, Peter (Canadian Jewish Studies / Études juives canadiennes, 2002)
By coincidence, on the evening of 9 November 1938,Kristallnacht, the Canadian Broadcasting Corporation broadcast from Winnipeg, as part of its “Ventures in Citizenship”series, a programme celebrating the contributions of Jews toCanadian life. “Ventures in Citizenship” was the brainchild ofRobert England, a prominent Great War veteran and writer onCanadian ethnic diversity, who was alarmed by the rise of NaziGermany and sought to promote good inter-group relations inCanada and to prepare for the stresses of war. The broadcasthighlighted the career of Lieutenant Myer Tutzer Cohen, whowas killed in action in November 1917 and was awarded theMilitary Cross.